2023
DOI: 10.1007/s10654-023-01009-0
|View full text |Cite
|
Sign up to set email alerts
|

Residential proximity to petrol stations and risk of childhood leukemia

Abstract: Petrol stations emit benzene and other contaminants that have been associated with an increased risk of childhood leukemia. We carried out a population-based case-control study in two provinces in Northern Italy. We enrolled 182 cases of childhood leukemia diagnosed during 1998–2019 and 726 age- and sex-matched population controls. We geocoded the addresses of child residences and 790 petrol stations located in the study area. We estimated leukemia risk according to distance from petrol stations within a 1000 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…A wide number of studies evaluated air pollution and childhood cancer risk by assessing whether living nearby heavy-traffic roads or proximity to industrial and urban sites is associated with an increased cancer risk. Numerous studies have found positive associations not only with leukemia, but also with CNS cancer, neuroblastoma, Wilms tumor, and bone cancer, among other cancers ( Table 2 ) [ 13 , 14 , 16 , 24 , 29 , 30 , 31 , 32 , 34 , 37 , 43 , 46 , 54 , 61 ]. However, other studies have found mild or negative associations [ 12 , 16 , 21 , 25 , 39 , 45 , 60 , 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…A wide number of studies evaluated air pollution and childhood cancer risk by assessing whether living nearby heavy-traffic roads or proximity to industrial and urban sites is associated with an increased cancer risk. Numerous studies have found positive associations not only with leukemia, but also with CNS cancer, neuroblastoma, Wilms tumor, and bone cancer, among other cancers ( Table 2 ) [ 13 , 14 , 16 , 24 , 29 , 30 , 31 , 32 , 34 , 37 , 43 , 46 , 54 , 61 ]. However, other studies have found mild or negative associations [ 12 , 16 , 21 , 25 , 39 , 45 , 60 , 185 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, certain behaviors, such as pica (placing hands and objects in one's mouth) and playing outside, increase children's odds of exposure (4). Regarding exposures in urban environments, residential proximity to petrol stations and industrial sites and exposure to mixtures of benzene, particulate matter ≤2.5 µm (PM 2.5 ), and polycyclic aromatic hydrocarbons (PAHs) from traffic emission are related to high risk of ALL (15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%